2020
DOI: 10.1016/j.jmmm.2019.165864
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diameter on the magnetic saturation in Fe84Cu16/MgO [0 0 1] multilayered islands

Abstract: Access to the published version may require subscription. N.B. When citing this work, cite the original published paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Earlier, it has been shown that for substrate temperature up to 100 • C Py/(1 Å) Cu showed a limited intermixing upon annealing [17]. The optimum substrate temperature for deposition obtained here is very close to 156 • C which has earlier been reported for the deposition of (001) Fe/MgO [38] and (001) Fe 84 Cu 16 /MgO [39] superlattices. We would like to remark that in our previous study we deposited 5 nm Ta underlayer to reduce the substrate surface roughness [13].…”
Section: Experimental Apparatus and Methodssupporting
confidence: 82%
“…Earlier, it has been shown that for substrate temperature up to 100 • C Py/(1 Å) Cu showed a limited intermixing upon annealing [17]. The optimum substrate temperature for deposition obtained here is very close to 156 • C which has earlier been reported for the deposition of (001) Fe/MgO [38] and (001) Fe 84 Cu 16 /MgO [39] superlattices. We would like to remark that in our previous study we deposited 5 nm Ta underlayer to reduce the substrate surface roughness [13].…”
Section: Experimental Apparatus and Methodssupporting
confidence: 82%
“…This finding challenges the traditional binary perspective of the MRAM operation, offering a new multi-level functionality in ultra-scaled MRAM cells [53]. While our study confirmed that a minor FM coupling of 0.01 mJ/m 2 at the MgO TB effectively suppresses back-hopping between FL 1 and FL 2 , and is significantly influenced by the crystalline quality, thickness, and stoichiometry of the MgO layers [54,55], it is crucial to note that our findings focused specifically on the IEC between these two layers. The potential for a similar FM coupling between the RL and FL 1 , through a MgO layer of the same thickness as that between FL 1 and FL 2 , requires separate consideration.…”
Section: Stack Amentioning
confidence: 58%
“…The interlayer coupling between the Fe layers is therefore not sufficiently strong to drive the order to an antiferromagnetic (AFM) state. The 90 configuration is metastable and enabled by the interplay between the strong four-fold magnetocrystalline anisotropy and the relatively much weaker antiferromagnetic interlayer exchange coupling 8 , 14 , 25 , 26 . The switching field is the field required to overcome the antiferromagnetic coupling and align the two layers.…”
Section: Resultsmentioning
confidence: 99%
“…Also roughness induced changes of the interlayer exchange coupling can be ruled out as it is constant (see supplementary information ). Finally, stray fields arising from the edges of the magnetic layers cannot be responsible for the observed changes with N, as they are negligible for thin films with large lateral dimensions ( 1 cm) 26 , 27 . We therefore need to look closer into the influence of the number on repeats on the switching field of the layers.…”
Section: Resultsmentioning
confidence: 99%